Black raspberry extract can lower serum LDL cholesterol via modulation of gut microbial composition and serum bile acid profile in rats fed trimethylamine-N-oxide with a high-fat diet - 임태환; 이기욱; 김련희; 차광현; 구송이; 문은채; 황금택 (한국식품과학회, 2022)
Blood trimethylamine-N-oxide (TMAO) has been associated with cardiovascular disease. Black raspberry (Rubus occidentalis, BR) has been regarded to be beneficial for cardiovascular health. This study aimed to investigate how BR extract affects serum lipid profile, gut microbial composition, metabolites in rats fed TMAO with a high-fat diet. Dietary TMAO increased serum LDL cholesterol, while BR extract decreased its level. α-Diversity of gut microbiota was not changed; however, in the rats fed TMAO, Macellibacteroides and Mucispirillum were enriched, while Ruminococcaceae was reduced. The BR supplementation could restore Macellibacteroides, Clostridium, and Ruminococcaceae. The BR supplementation increased cecal hippuric acid and serum farnesoid X receptor-antagonistic bile acids, including ursodeoxycholic acid (UDCA), tauro-α-muricholic acid, and tauro-UDCA. The BR supplementation tended to upregulate Cyp7a1 and Abcg5 expressions while downregulating Srebf2 and Hmgcr expressions. BR extract affects the gut bacterial community and microbial metabolites, lowering serum LDL cholesterol in rats with elevated serum TMAO.